PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Herfin Angelina; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to examine going concern audit opinion affected liquidity, leverage, effectiveness of the audit committee, audit tenure, audit delay and opinion shopping to going concern audit opinion on banking industries. Variables used in the examination are liquidity, leverage, effectiveness of the audit committee, audit tenure, audit delay and opinion shopping as the independent variables, also going concern audit opinion as the dependent variable. This research used manufacturing companies during the 2018-2020 with a total sample size of 129 samples. Sampling based on a purposive sampling method that follows certain criteria(s). Logistic regression analysis is the analysis method used in this research. The results of this study indicates that leverage and audit delay have a positive significant effect on going concern audit opinion. Effectiveness of the audit committee has a negative and significant effect on going concern audit opinion. Liquidity, audit tenure and opinion shopping have no on going concern audit opinion.